2012
DOI: 10.1002/pssa.201228252
|View full text |Cite
|
Sign up to set email alerts
|

Modification of metal–organic interface using F4‐TCNQ for enhanced hole injection properties in optoelectronic devices

Abstract: Incorporation of thin layers of tetrafluro‐tetracyanoquinodimethane (F4‐TCNQ) has been found to modify the work functions of a number of substrates. Surface potential measurement using Kelvin probe method (KPM) has been used to monitor the change in work function of the modified substrates. The results support the integer charge transfer model by which the Fermi levels of the substrates are aligned with the negative polaron states of F4‐TCNQ. Further, we found that the work function of the substrates increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The almost rigid shift induced by moderate F 4 -TCNQ doping could be interpreted by several reported mechanisms, including the integer charge transfer model [ 16 , 18,19 ] the energy level hybridization model, [ 20,21 ] and the effective electrode work function modifi cation due to the diffusion of F 4 -TCNQ molecules through the NPB host layers to the electrode/organic interface. [ 26,27 ] In all these three cases, the reduced HIBs (by ≈0.6 eV) will be capable of dramatically decreasing the drive voltage for devices with F 4 -TCNQ doping. In addition, the HIBs of doped DMFL-NPB and DPFL-NPB fi lms are still ≈0.1 eV lower than that of doped NPB fi lm.…”
Section: Molecular Structure Dependent Electronic Structuresmentioning
confidence: 96%
“…The almost rigid shift induced by moderate F 4 -TCNQ doping could be interpreted by several reported mechanisms, including the integer charge transfer model [ 16 , 18,19 ] the energy level hybridization model, [ 20,21 ] and the effective electrode work function modifi cation due to the diffusion of F 4 -TCNQ molecules through the NPB host layers to the electrode/organic interface. [ 26,27 ] In all these three cases, the reduced HIBs (by ≈0.6 eV) will be capable of dramatically decreasing the drive voltage for devices with F 4 -TCNQ doping. In addition, the HIBs of doped DMFL-NPB and DPFL-NPB fi lms are still ≈0.1 eV lower than that of doped NPB fi lm.…”
Section: Molecular Structure Dependent Electronic Structuresmentioning
confidence: 96%
“…ARTICLE already reported. 28,29 When coadsorbed with molecular donors, it reduces the hole-injection barrier between Au electrodes and several organic semiconductors. 30,31 We then consider the doubly substituted 2,5-difluoro-7,7,8,8-tetracyanoquinodimethane (F2-TCNQ, A = 4.59 eV) and fluoro-7,7,8,8-tetracyanoquinodimethane (F-TCNQ, A = 4.55 eV), where only one H is replaced (see the SI for the molecular structures on the substrate).…”
Section: Articlementioning
confidence: 99%
“…28 Both molecules have been routinely used to decrease the hole injection barrier at the metal–organic interface either by doping the hole transport layer or as an intermediate buffer layer between the hole transport layer and the metal anode. 2932 Recently, it has also been shown that doping the electron injection layer with TCNQ 33 or inserting a TCNQ buffer layer between the electron transport layer and the metal cathode 34 can also improve the performance of organic light-emmiting devices.…”
Section: Introductionmentioning
confidence: 99%